The Condensed Handbook of Measurement and Control - Batthika, N.E (ISA, 2018)
Intro -- The Condensed Handbook of Measurement and Control -- Table of Contents -- c -- Preface -- Chapter 1 -- Chapter 2 -- Table 2-1 . Identification Letters Note: Numbers in parentheses refer to following explanatory notes. -- Figure 2-2. Line Symbols Note: Numbers in parentheses refer to the following explanatory notes. -- Figure 2-3. Device and Function Symbols Note: Numbers in parentheses refer to the following explanatory notes. -- Chapter 3 -- Table 3-1 . Analyzer Comparison -- Table 3-2 . Troubleshooting Guide -- Chapter 4 -- Table 4-1 . Flow Measurement Comparison -- Table 4-1. Flow Measurement Comparison (continued) -- Chapter 5 -- Table 5-1 . Level Measurement Comparison -- Chapter 6 -- Table 6-1 . Pressure Measurement Comparison -- Chapter 7 -- Table 7-1 . Temperature Measurement Comparison -- Table 7-2 . Partial Type K Thermocouple Temperature-EMF Table -- Chapter 8 -- Chapter 9 -- Chapter 10 -- Table 10-1 . Safety Integrity Level Performance Requirements -- Table 10-2 . Risk Severity: Example -- Table 10-3 . Risk Frequency: Example -- Table 10-4 . Overall Risk: Example -- Chapter 11 -- Table 11-1 . Standing Body Dimensions -- Table 11-2 . Seated Body Dimensions -- Chapter 12 -- Chapter 13 -- Table 13-1 . Control Valve Comparison -- Chapter 14 -- Chapter 15 -- Table 15-1. Installation Completion Status Note 1: Refer to Chapter 16 for activities checked by the contractor prior to the final checkout done jointly by plant personnel and the contractor. -- Chapter 16 -- Chapter 17 -- Chapter 18 -- Chapter 19 -- Chapter 20 -- Table 20-1. Decision Analysis -- Chapter 21 -- Appendix A -- Table A-1. Multiples and Submultiples of SI Units -- Table A-2. SI Base Units -- Table A-3. SI Supplementary Units -- Table A-4. SI Derived Units with Special Names -- Table A-5. Examples of SI Derived Units without Special Names